2020
DOI: 10.3390/su12062517
|View full text |Cite
|
Sign up to set email alerts
|

The Linkages of Carbon Spot-Futures: Evidence from EU-ETS in the Third Phase

Abstract: Based on the prices selected from European Energy Exchange (EEX) from 2013 to 2018, we investigate the inter-correlation of carbon spot and futures markets. Specifically, we adopt the widely used DCC-GARCH model and VAR-BEKK-GARCH model to conduct a comprehensive analysis on the carbon market, i.e., the dynamic correlation and volatility spillover between carbon spot and carbon futures. Moreover, we develop a hedge strategy based on the VAR-BEKK-GARCH model and calculate the hedging effectiveness (HE) value to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…Bollerslev improved the model and proposed the GARCH model, which solved the problem of many lag periods [22]. For the study of volatility spillover effect among financial markets, the most common method used by scholars at home and abroad is the multivariate GARCH model [23][24][25][26]. Li et al found that the multivariate GARCH model can cover multiple factors affecting the market at the same time and provide more information so as to more comprehensively describe the volatility spillover effect between multiple markets [27].…”
Section: Methodsmentioning
confidence: 99%
“…Bollerslev improved the model and proposed the GARCH model, which solved the problem of many lag periods [22]. For the study of volatility spillover effect among financial markets, the most common method used by scholars at home and abroad is the multivariate GARCH model [23][24][25][26]. Li et al found that the multivariate GARCH model can cover multiple factors affecting the market at the same time and provide more information so as to more comprehensively describe the volatility spillover effect between multiple markets [27].…”
Section: Methodsmentioning
confidence: 99%
“…The findings of Silvapulle and Moosa (42) discovered the bi-directional non-linear Granger causalities between spot and futures prices in the WTI (West Texas Intermediate) crude oil market. Chen et al (5) focused on the relationships between the carbon spot and futures. Other studies focused on hedging between markets.…”
Section: Related Literaturementioning
confidence: 99%
“…Thereafter, the DCC specification is adopted by numerous investigations to depict the correlation between assets. The DCC model can be summarized by the following Equations (3)(4)(5)(6).…”
Section: Dcc-garch Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Different from the literature concerning the traditional fossil fuel energy, D'Adamo [17] notes that new energy, such as photovoltaic resources, could drive the clean global economy of the future and also affect the price of EU CET market. Besides, Chen et al [18] find that CET future market prices could exert an influence on the spot market price too. Through a linear regression model analysis, D'Adamo [19] reveals that the relationship between the circular economy and the price of CO 2 is currently low.…”
Section: Literature Reviewmentioning
confidence: 99%